Epithelioid Hemangioendothelioma: Incidence, Mortality, Prognostic Factors, and Survival Analysis Using the Surveillance, Epidemiology, and End Results Database. (16th September 2022) - Liu, Zhen; He, Shuting
Abstract : Background. Although epithelioid hemangioendothelioma (EHE) is a rare and aggressive vascular tumor, its demographic characteristics remain unclear. We used the surveillance, epidemiology, and end results (SEER) database to determine the clinical features, incidence, and prognostic factors associated with overall survival in patients with EHE. Methods. The demographic and clinical data of patients with EHE were extracted from the SEER database (1975-2019) to calculate the incidence of EHE and survival rate in these patients. The Cox proportional hazards model and Kaplan-Meier method were used to analyze the prognostic factors of overall survival in these patients. A nomogram and time-dependent receiver operating characteristic (ROC) curve were employed to predict the 3- and 5-year survival rate. Results. The overall incidence rate (IR) of EHE was 0.230 (95 % confidence interval CI = 0.201 – 0.263 ) per 1, 000, 000 person-years. According to the age-stratified IR, the highest age-adjusted IR was observed in patients aged 60–79 years (0.524 per 1, 000, 000 person-years, 95 % CI = 0.406 – 0.665 ). The majority (30.8%) of the tumors were located in the soft tissue and skin, followed by lesions in the abdomen (28%), respiratory system (19%), bone and joint (8.6%), and others. The 5-year overall survival rate was 55.6% (95 % CI = 32.8 – 73.5 % ). Multiple Cox regression analysis revealed that age >80 years (hazard ratio HR = 8.57, 95 % CI = 2.32 – 31.63, P < 0.001 ), African-American race (HR = 2.52, 95 % CI = 1.31 – 4.85, P < 0.01 ), "American Indian/Alaska Native" or "Asian or Pacific Islander" (HR = 2.99, 95 % CI = 1.5 – 5.96, P < 0.01 ) race, and respiratory tumors (HR = 2.55, 95 % CI = 1.37 – 4.75, P < 0.01 ) were distinctly related to worse overall survival. The calibration plots demonstrated good consistency between nomogram-predicted and actual survival. The area under the time-dependent ROC curve was 0.721 (95 % CI = 0.63 – 0.81 ) and 0.719 (95 % CI = 0.63 – 0.81 ) for the 3- and 5-year survival, respectively. For the convenience of researchers and clinicians, we designed an online dynamics nomogram to predict the survival rate. Conclusion. EHE is a relatively rare vascular tumor, which principally occurs in the soft tissue and skin. It most commonly occurs in patients aged 60–79 years and its incidence has increased in recent years. Age at diagnosis, race, and tumor location may affect the overall survival outcomes.